THE RELEVANCE OF RAISING AWARENESS OF PHARMACEUTICAL WORKERS ON HIV INFECTION - Андрей Георгиевич Петров; Галина Тихоновна Глембоцкая; Ольга Владимировна Хорошилова; Сергей Николаевич Филимонов; Виктор Андреевич Семенихин (Медицина в Кузбассе, 2023)
Disclosure of the professional capabilities of pharmaceutical workers in the field of prevention and anti-epidemic work of HIV infection (infection caused by human immunodeficiency virus) is possible only through raising awareness of pharmaceutical workers on this problem. Currently, the issues of HIV infection are very relevant, due to the adverse reactions that occur in patients after taking medications. This fact associated with undesirable reactions should not be ignored, due to the fact that responsible participants in the retail pharmaceutical market fully perform their function in the system of specialized pharmaceutical care. One of the key components of the awareness-raising system on this problem are pharmaceutical workers, or rather employees of pharmacy organizations directly interacting with consumers of medicines. However, according to information from available literature sources and our research, there is a problem of low awareness among pharmacy workers about HIV infection. The aim of the study is to raise awareness of pharmaceutical workers working in pharmacy organizations on HIV infection, aimed at health promotion and disease prevention. Material and methods. The object of research in the study of this problem are pharmaceutical workers (n = 250). For this purpose, an original questionnaire of a specialist has been developed for sociological research. The study was conducted using the method of expert assessments and their programmatic statistical processing in the Statistica 10 program. Results. The results of a survey with the participation of 250 pharmaceutical workers of pharmacy organizations in Kemerovo showed that pharmacists and pharmacists have insufficient knowledge on the prevention and treatment of HIV infection. Qualitative and quantitative facts have been identified that allow us to conclude that pharmaceutical workers are not sufficiently aware of HIV infection, including various directions concerning ways of infection, prevention, treatment, and compliance with the drug regimen. To form and raise awareness among pharmaceutical workers in the field of HIV prevention and treatment, it is necessary to use various interactive learning technologies, such as conferences, seminars, round tables, working with documents.